2006
DOI: 10.1152/ajprenal.00304.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras/ERK1/2 signaling protects against postischemic renal injury

Abstract: The small GTPase p21 Ras and its downstream effectors play a central role in the control of cell survival and apoptosis. We studied the effects of Ras/ERK1/2 signaling inhibition on oxidative damage in cultured renal and endothelial cells and on renal ischemia-reperfusion injury in the rat. Primary human renal tubular and human endothelial ECV304 cells underwent significant cell death when subjected to oxidative stress. This type of stress induced robustly ERK1/2 and phosphoinositide 3-kinase (PI3-kinase) sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
(32 reference statements)
4
46
0
2
Order By: Relevance
“…[165][166][167][168] Serum and urine levels of miR-21 also predicted the progression of AKI in cardiac surgery patients. 169 In an in vivo mouse model study, renal ischemia reperfusion caused the increase of several miRNA molecules in plasma and kidneys when compared with sham-treated mice, at 3 hours, 6 hours and 24 hours following the ischemic injury.…”
Section: Microrna Molecules As Potential Biomarkers Of Ci-akimentioning
confidence: 98%
“…[165][166][167][168] Serum and urine levels of miR-21 also predicted the progression of AKI in cardiac surgery patients. 169 In an in vivo mouse model study, renal ischemia reperfusion caused the increase of several miRNA molecules in plasma and kidneys when compared with sham-treated mice, at 3 hours, 6 hours and 24 hours following the ischemic injury.…”
Section: Microrna Molecules As Potential Biomarkers Of Ci-akimentioning
confidence: 98%
“…23 Blood pressure was measured under basal conditions and after the administration of the following treatments: acetylcholine (ACh) (1 g/kg body weight [BW] intraperitoneal [IP]), sodium nitroprusside (SNP) (2 g/kg BW IP), db-cGMP (5 mg/kg BW IP), N G -nitro-L-arginine methyl ester (L-NAME) (20 mg/kg BW per day, drinking water for 2 weeks), 1H- [1,2,4]oxadiazole [4,3-a]quinoxalin-1-one (ODQ) (5 mmol/kg BW IP), DT-3 (500 g/kg BW IP), and chaetomellic acid A (1.5 mg/kg BW IP at 24 and 16 hours before blood pressure measurement and euthanasia). 24 …”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…ERK1/2 is also activated by cell stressors, including reactive oxygen species. In a study utilizing H 2 O 2 injury in human renal cells, ERK1/2 inhibition was shown to decrease necrosis and apoptosis (5), whereas in a cisplatin-induced cell injury model, ERK1/2 inhibition reduced caspase 3 activation and apoptosis (6). In renal proximal tubular cells (RPTC), phosphorylated ERK1/2 was shown to reduce mitochondrial respiration and ATP production by decreasing complex I electron transport chain activity in response to tert-butyl hydroperoxide (TBHP), a model oxidant (7).…”
mentioning
confidence: 99%